Going beyond tradition: Estimating residential electricity demand using an appliance index and energy services - Nina Boogen; Souvik Datta; Massimo Filippini (ETH Zurich, CER-ETH - Center of Economic Research, 2014)
In this paper we estimate the long- and short-run price elasticities of residential electricity consumption in Switzerland from a household survey by constructing an index of the stock of household appliances as well as by using energy services. We create the index by aggregating the information on the major household appliances. The index is used to estimate the impact of appliances on residential electricity demand. Furthermore, we also use energy services to estimate the electricity demand. We adopt an instrumental variables approach to obtain consistent estimates of the price elasticity to account for potential endogeneity concerns with the average price as well as the appliance index. Our results suggest that the price elasticity is around -0.6. We conclude that Swiss households are price inelastic in electricity prices. This can be used for policy makers as well as by utility companies to design pricing instruments to modify electricity consumption. We also find that estimates of the electricity demand when we substitute the usual residential characteristics with energy services are quite comparable.
Keywords: D; D1; Q; Q4; Q5; 330; Residential electricity; appliance stock index; energy services; instrumental variables